Customer satisfaction and competitiveness in the Chinese E-retailing: structural equation modeling (SEM) approach to identify the role of quality factors - Subramanian, Nachiappan; Gunasekaran, Angappa; Yu, Jie; Cheng, Jiang; Ning, Kun (Elsevier, 2014)
This paper attempts to study the impact of customer satisfaction and the Chinese electronic retailers (E-retailers) competitiveness using quality factors. Two conceptual models based on asset-process-performance (APP) competitive theoretical framework have been proposed. The proposed models include E-retailers strategic factors such as logistics, quality and customer satisfaction equivalent to asset, process and performance entities of the APP framework. Using an empirical survey from a young population, this study, with the support of structural equation modeling (SEM) identifies reliability in service quality and purchasing experience in e-service quality as dominant customer satisfaction factors. This study uses both exploratory and confirmatory factor analysis and suggests that to be competitive Chinese E-retailers have to focus more on the delivery of products (logistics) compared to other intangible service quality factors. On theoretical front, this study is a novel attempt to validate the APP framework for E-retailers’ competitiveness. On the practical front, the outcome of the study would be highly beneficial to the Chinese E-retailers to fine tune their strategy to satisfy the growing demand. Furthermore, this study can supplement government policy makers to regulate the growing volatile market.